Microvascular alterations detected by optical coherence tomography angiography in non‐arteritic anterior ischaemic optic neuropathy: a meta‐analysis. Issue 2 (21st June 2021) - Chou, Yuyu; Zhang, Bilei; Ma, Jin; Zhong, Yong
Abstract: Purpose: To evaluate microvascular alterations with optical coherence tomography angiography (OCTA) in eyes with non‐arteritic anterior ischaemic optic neuropathy (NAION) and the unaffected fellow eyes. Design: Systematic review and meta‐analysis. Methods: A comprehensive literature search was conducted in the PubMed and Embase databases through 6 September 2020, to identify the studies on NAION and the unaffected fellow eyes using OCTA. Eligible studies and data of interest were extracted and analysed by RevMan Software v. 5.4 and Stata Software v.14.0. The weighted mean differences and 95% confidence intervals were used to assess the strength of the association. Results: Seventeen observational comparative studies, including 379 eyes with NAION, 175 unaffected contralateral eyes and 470 eyes of healthy controls, were identified. Compared to those of the healthy controls, the perfusion density (PD) of radial peripapillary capillary (RPC) and peripapillary superficial capillary plexus (ppSCP) of NAION were significantly lower. Moreover, the PD of the macular SCP (mSCP) in NAION was significantly reduced in the whole image, superior quadrant and temporal quadrant, while the macular deep capillary plexus (mDCP) showed a decreasing PD only within the whole image. Between unaffected fellow eyes and healthy eyes, significant differences of PD were demonstrated in the whole image and some peripapillary regions of the RPC and ppSCP. Conclusion: Our results suggested that compared to those of healthy controls, the eyes affected by NAION and unaffected fellow eyes demonstrated significant microvascular impairments in different regions. Between acute and non‐acute NAION, macular OCTA parameters showed different characteristic patterns.